2005
DOI: 10.1099/mic.0.27888-0
|View full text |Cite
|
Sign up to set email alerts
|

Functions of the siderophore esterases IroD and IroE in iron-salmochelin utilization

Abstract: The siderophore salmochelin is produced under iron-poor conditions by Salmonella and many uropathogenic Escherichia coli strains. The production of salmochelin, a C-glucosylated enterobactin, is dependent on the synthesis of enterobactin and the iroBCDEN gene cluster. An E. coli IroD protein with an N-terminal His-tag cleaved cyclic salmochelin S4 to the linear trimer salmochelin S2, the dimer salmochelin S1, and the monomers dihydroxybenzoylserine and C-glucosylated dihydroxybenzoylserine (salmochelin SX, pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 20 publications
4
118
1
Order By: Relevance
“…Although the similarity of IroC to ABC-type efflux proteins is significant, growth promotion studies indicated that IroC might be responsible for the uptake of linearized forms of Fe-salmochelin and Fe-enterobactin (359). Thus, two conflicting models of salmochelin utilization currently exist, one assigning IroC as a salmochelin exporter (95,191) and the other one assigning IroC as an importer of the iron-charged linearized salmochelin trimer (359). IroC-dependent Fe-salmochelin transport studies or iroC mutant phenotype analyses might help to clarify the opposing interpretations.…”
Section: General Steps Of Siderophore Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the similarity of IroC to ABC-type efflux proteins is significant, growth promotion studies indicated that IroC might be responsible for the uptake of linearized forms of Fe-salmochelin and Fe-enterobactin (359). Thus, two conflicting models of salmochelin utilization currently exist, one assigning IroC as a salmochelin exporter (95,191) and the other one assigning IroC as an importer of the iron-charged linearized salmochelin trimer (359). IroC-dependent Fe-salmochelin transport studies or iroC mutant phenotype analyses might help to clarify the opposing interpretations.…”
Section: General Steps Of Siderophore Pathwaysmentioning
confidence: 99%
“…Since it was observed that E. coli fepB mutants that possess the iroA locus were still able to utilize salmochelin as an iron source, it was concluded that IroC, the only CM permease encoded in the iroA cluster, might be responsible for Fe-salmochelin uptake (359). Direct evidence for IroC function, however, for its role in uptake or in secretion does not exist so far.…”
Section: General Steps Of Siderophore Pathwaysmentioning
confidence: 99%
“…1B), which is also found in pathogenic strains of E. coli, Salmonella spp., and K. pneumoniae (9)(10)(11)(12). The iroA gene cluster encodes five proteins involved in modification and transport of Ent: IroB Cglucosylates Ent (13), IroE hydrolytically linearizes Ent (14,15), IroD degrades ferric complexes of the siderophore to release iron in the bacterial cytoplasm (14,15), and IroN and IroC transport Ent and its derivatives (16). Rather than Ent, iroAharboring bacteria secrete a mixture of salmochelins S4 and S2 ( Fig.…”
mentioning
confidence: 99%
“…The transport of salmochelin is still under investigation, and the functional role of IroC is disputed. The IroC protein has been implicated as a inner membrane exporter (Baumler et al, 1996) and an inner membrane importer (Zhu, Valdebenito, Winkelmann, & Hantke, 2005). We have illustrated the former model where salmochelin is exported through the inner membrane protein IroC, and then shuttled across the periplasmic space and secreted through the outer membrane via an unknown mechanism.…”
Section: Discussionmentioning
confidence: 96%